Keabsahan Klausula Baku Pada Struk Pembayaran Menurut Hukum Perjanjian Islam Dan UU No.8 Tahun 1999 Tentang Perlindungan Konsumen - Dina Silvana Rochimatul Ummah (Journal of Islamic Business Law, 2018)
The research discusses validity of standard clause “Items purchased can not be exchanged or returned" on the payment receipt based The Islamic Contract Law and Law No. 8 of 1999 on Consumer Protection. The type of research use is normative legal research with the statute approach and conceptual approach. Sources of legal materials are analyzed by methods of grammatical interpretation, systematic interpretation, and broad interpretation. The result of the research shows that the aspect of the standard clause on the payment receipt is relevant to the Islamic Contract Law, because it is in accordance with the concept of principle contract which is regulated in KHES, namely good faith principle, ikhtiyati principle, amanah principle, Luzum principle, principle of ease, principle of the lawful cause, and the written principle. However, there are aspects that are not in accordance with the principle of contract in KHES, namely the principle of ikhtiyari, taswiyah principle, mutual benefit principle, transparency principle, and al-hurriyah principle. Meanwhile, according to UUPK, the standard clause in the payment receipt is classified in the exemption clause. However, the exemption clause still provides protection to the consumer in the fulfillment of the right of the consumer to obtain compensation payment of damages suffered due to the use of good. It’s because the principle of absolute responsibility and the principle of responsibility for the element of error imposed to the business actor